Soil Quality Parameters of Upland Agroecosystem under Various Agricultural Land Uses in Sabal, Sarawak, Malaysia. - Ho, Soo Ying (Universiti Malaysia Sarawak (UNIMAS), 2021)
Uplands are defined as the area located on the slopes of hilly landscapes. Rapid land use change at the upland areas of Sarawak, Malaysia lead to the transition of subsistence agriculture to semi-subsistence agriculture, giving rise to the formation of diversified upland agriculture which consists of shifting cultivation and cash crop cultivation. Often, recent agricultural practices involved short fallow length, establishment of permanent farmlands and extensive use of agrochemicals in the farming practices. In fact, naturally infertile sandy soils were also utilized for agricultural purposes. Yet, the outcome of such practices on the quality of soil at the upland agroecosystem did not receive much attention in Sarawak. Hence, the general objective of the present study was to determine the soil quality parameters of upland agroecosystems under various agricultural land uses in Sarawak, Malaysia. The first specific objective was to characterize the soil physicochemical properties of intensified shifting cultivation practices. Two types of upland rice land uses, namely single cultivation (SC) and multiple cultivation (MC) sites were selected. Before burning, soil pH was highly acidic in SC sites while MC sites showed less acidity with relatively high Mg and Ca. The level of soil K, Mg, Ca and P increased after burning practices in SC sites. However, MC sites showed lower to no increase in nutrient contents, partly attributed to the higher nutrient export from soils due to rice harvest and lesser input of SOM to soil from frequent burning. Agrochemicals application in MC sites was necessary to restore the depleted soil nutrients after successive cultivation for sustaining rice production. Secondly, this study also attempts to evaluate the soil physicochemical properties of sandy-textured soils under smallholder agricultural land uses (i.e. secondary forest, rubber, pepper, oil palm). Soil Total C was the important determinant of fertility for sandy-textured soils under all land uses. Nonetheless, insufficient K input was observed in oil palm land uses while excessive P and K did not vii retain in the soils under pepper land use, indicating the characteristics of poor nutrient retention capacity of siliceous sandy-textured soils. In order to elucidate the impact of present smallholder agricultural land uses, soil erosion and surface runoff were determined using microrunoff plot approach. Our findings showed nutrients (P and K) present abundantly in runoff water from oil palm and pepper land uses. With reference to the results in rubber and secondary forests, dynamics of vegetation cover and ground cover appeared as a key factor in controlling and mitigating the erosional response of the smallholder agricultural land uses. The rate of erosion events within smallholder land uses in the study area was negligible with minimal impact to the surrounding agro-environment. The last objective of the study was to propose the integrated use of organic fertilizers, oil palm empty fruit bunch (OPEFB) compost to reduce the reliance on inorganic (chemical) fertilizer in the present farming practices. The results showed that the addition of OPEFB compost reduced the use of inorganic fertilizers to as low as 25% to achieve the minimum recommended yield. Likewise, the soil Total C, Total N and nutrient contents were also improved after the cultivation, suggesting the role of organic fertilizers as soil ameliorant to improve the soil fertility. In general, the present land uses among smallholder farmers in upland areas of Sabal,Sarawak did not bring adverse effect to the surrounding environment. Considering the microclimate condition, attentive land use planning and integrated nutrient management as well as combined efforts from various parties such as government, local people, agriculture groundstaffs and researchers are necessary towards sustainable upland agriculture in Sarawak, Malaysia.